The Analysis of Translation Technique in Abstracts of National Accredited Journals - Rezita, Reza; Maisarah, Ira; Sujarwati, Iis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
This study investigated the types of translation techniques. This study used mixed methods research design. The data that obtained was the translation techniques. This approach chose because to investigate the techniques that were used by authors in translating abstract of National Accredited Journal and to find out the differences between techniques that were used by authors in translating abstract in high, medium, and low National Accredited Journal. Abstracts were obtained from the National Journal of education included in high (1 or 2 index), medium (3 or 4 index), and low (5 or 6 index). The instrument of the research was Document Analysis Table. To collect the data, the researcher examined the cultural terms for both the original language and the target language. For analyzing the data, the researcher used 4 steps data reduction, data display, drawing conclusion, and data coding. The result portrayed that established equivalent with 29 data (25.2%) was most dominant. It is probably because the translator chose to use an already established and equivalent term in the target language. In translating the terms and sentence the result described that in High Level and Middle Level, there has been found more various translation technique than abstract in Low Level National Accredited Journal.